Glacial melting: An overlooked threat to Antarctic krill - Fuentes, Verónica Lorena; Alurralde, Roque Gastón; Meyer, Bettina; Aguirre, Gaston Ezequiel; Canepa, Antonio; Wölf, Anne Cathrin; Hass, H. Christian; Williams, Gabriela Noemí; Schloss, Irene Ruth (Scientific Reports)
Strandings of marine animals are relatively common in marine systems. However, the underlying mechanisms are poorly understood. We observed mass strandings of krill in Antarctica that appeared to be linked to the presence of glacial meltwater. Climate-induced glacial meltwater leads to an increased occurrence of suspended particles in the sea, which is known to affect the physiology of aquatic organisms. Here, we study the effect of suspended inorganic particles on krill in relation to krill mortality events observed in Potter Cove, Antarctica, between 2003 and 2012. The experimental results showed that large quantities of lithogenic particles affected krill feeding, absorption capacity and performance after only 24 h of exposure. Negative effects were related to both the threshold concentrations and the size of the suspended particles. Analysis of the stomach contents of stranded krill showed large quantities of large particles ( > 106μm3), which were most likely mobilized by glacial meltwater. Ongoing climate-induced glacial melting may impact the coastal ecosystems of Antarctica that rely on krill. Fil: Fuentes, Verónica Lorena. Consejo Superior de Investigaciones Científicas. Instituto de Ciencias del Mar; España. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Alurralde, Roque Gastón. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto de Diversidad y Ecología Animal. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Instituto de Diversidad y Ecología Animal; Argentina Fil: Meyer, Bettina. Helmholtz Centre for Polar and Marine Research. Alfred Wegener Institute; Alemania. University of Oldenburg; Alemania Fil: Aguirre, Gaston Ezequiel. Helmholtz Centre for Polar and Marine Research. Alfred Wegener Institute; Alemania. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Canepa, Antonio. Pontificia Universidad Católica de Valparaíso; Chile Fil: ...